2023
DOI: 10.3390/microorganisms11040984
|View full text |Cite
|
Sign up to set email alerts
|

Cefiderocol-Based versus Colistin-Based Regimens for Severe Carbapenem-Resistant Acinetobacter baumannii Infections: A Propensity Score-Weighted, Retrospective Cohort Study during the First Two Years of the COVID-19 Pandemic

Abstract: Background. A large increase in multi-drug-resistant Acinetobacter baumannii, especially carbapenem-resistant strains, occurred during the first two years of the COVID-19 pandemic, posing important challenges in its treatment. Cefiderocol appeared to be a good option for the treatment of Carbapenem-resistant Acinetobacter baumannii (CR-Ab), but to date, the guidelines and evidence available are conflicting. Methods. We retrospectively included a group of patients with CR-Ab infections (treated with colistin- o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
(67 reference statements)
1
23
1
Order By: Relevance
“…These results are inconsistent with other studies, such as the cohort from Mazzitelli, study involving 111 patients with Carbapenem-Resistant Acinetobacter baumannii infections [ 16 ]. This study showed a higher, yet not statistically significant, mortality rate in the cefiderocol group compared to the colistin group (51% vs. 37%, p = 0.130).…”
Section: Discussioncontrasting
confidence: 88%
“…These results are inconsistent with other studies, such as the cohort from Mazzitelli, study involving 111 patients with Carbapenem-Resistant Acinetobacter baumannii infections [ 16 ]. This study showed a higher, yet not statistically significant, mortality rate in the cefiderocol group compared to the colistin group (51% vs. 37%, p = 0.130).…”
Section: Discussioncontrasting
confidence: 88%
“…Nonetheless, very recent reports of cefiderocol-based regimens suggest that the guidelines and evidence in the treatment of CRAB infections are conflicting. The outcome and safety profile did not differ significantly from the colistin regimen given to the patients [47,48].…”
Section: Therapeutic Indicationsmentioning
confidence: 75%
“…Indeed, in recent years, and with the clinical approval of cefiderocol in diverse countries, it has been shown that this siderophore-cephalosporin has been effective in MDR infections, with a higher activity than ceftazidime-avibactam and meropenem [43]. Nonetheless, others reports point to a similar activity and safety profile to colistin in the treatment of CRAB infections [47]. More real-world studies are needed to settle accurate guidelines in the clinical picture.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…While the above two studies [ 33 , 34 ] are the only randomised studies until today, there have been a significant number of studies performed in recent years [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ], and we present these data in Table 2 . Most of these studies were conducted in Italy and are retrospective in nature.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these studies were conducted in Italy and are retrospective in nature. A total of 744 patients were included in the studies in the table [ 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] that addressed the therapeutic management of VAP and bloodstream carbapenem-resistant A. baumannii (CRAB) infections. When examining the mortality of patients that received a cefiderocol-containing regimen versus a comparator regimen that did not contain cefiderocol, mortality was observed in 152 out of the 367 patients (41.4%) that received cefiderocol versus 247 out of the 430 patients (57.4%) that received a comparator antibiotic.…”
Section: Resultsmentioning
confidence: 99%